AN OVERVIEW OF THE MAIN WAYS TO IMPROVE THE ADS-B SYSTEM SECURITY - V. V. Kosianchuk; N. I. Selvesiuk; R. R. Khammatov (Научный вестник МГТУ ГА, 2019)
Automatic dependent surveillance of broadcasting type (ADS-B) is an important means of ensuring the safety and efficiency of air traffic. In the future, the role of ADS-B will increase. At the same time, the cyber security of ADS-B is clearly insufficient. The article analyzes the problem of low security of ADS-B. The main reasons for the vulnerability of ADS-B are the system openness and modern achievements in the development of computer technology and software defined radio (SDR).The classification of probable attacks on the ADS-B system with the goals determination, complexity of implementation and damage from the attack is given. It is concluded that other aviation radio-technical systems possess similar vulnerabilities and require a comprehensive solution to the problem of increasing the security level. The main reasons for insufficient security of aviation communication, navigation and surveillance systems are: long development and certification cycles, legacy and compatibility requirements, price pressure, frequency overloads and the preference for open systems. The paper gives an overview of the main ways to improve the ADS-B system security. It is shown that all methods of improving security can be divided into two groups: methods based on the identification and authentication of broadcast radio networks subscribers and methods based on the verification of data transmitted over broadcast radio networks by unidentified subscribers. The methods of the first group implement algorithms of the "identification-authentication" type and can be divided into non-cryptographic and cryptographic; the latter can use symmetric or asymmetric encryption. The methods of the second group are based on various algorithms for data verification from the ADS-B system with some additional data obtained through other channels or other sources. The methods of the second group are considered: multilateration, distance restriction, Kalman filtering, statistical hypothesis testing, group verification, reasonableness check and the use of additional data. The article provides the examples of using some methods to improve the security of the ADS-B system, their advantages and disadvantages.